An Algorithm for Labeling Topological Maps to Represent Point of Interest for Vision Impaired Navigation - Jayakody, Jayakody Arachchilage Don; Murray, Iain; Herrmann, Hannes (2015)
Navigation in indoor environments is highly challenging for both vision impaired and sighted people, particularly in unknown environments visited for the first time. Several solutions have been implemented and proposed to deal with this challenge. Although some of them have shown to be useful in real scenarios, each solution involves a significant deployment effort or describes objects in a manner that is unfamiliar or incomprehensible to an individual with severe blindness. This paper presents a model of adding informational point of interest to the typical indoor topological map; with particular attention to the semantic labels of the different type of indoor places and proposes a simple way to include the tags to build the topological map. Using this POI and the semantic information, the system determines the user's path, locates possible obstacles on that route, and offers navigation information to assist vision impaired navigation.